Consumer Protection of Flight Services through Corporate Social Responsibility Implementation in Indonesia (Faculty of Law, Universitas Negeri Semarang, 2020)
In Indonesia, air transportation is one type of transportation that is needed by the community in meeting their needs. Therefore, the rapid development of airlines makes competition among airline service companies, among others, provide various promotions to attract consumers to attract as many passengers as possible. However, in the implementation of service quality is still neglected by the company, which can be detrimental to consumers (passengers). This research is a normative legal research using a statutory approach and conceptual approach. The results of this study indicate that the airline service companies in protecting consumers must comply with the Consumer Protection Law and can through the implementation of CSR programs. Some CSR implementations by PT. Garuda Indonesia Regarding Consumer Protection is passenger safety, product and service information, customer complaints service, customer sound management (compliment, suggestion, complaint), and service improvement through a representative office.